Successful pulmonary arteriovenous malformation closure using MFO in child - Lasmono, Shirley Ferlina; Rachman, Mahrus A.; Utamayasa, I Ketut Alit; Hidayat, Taufiq (Acta Biomedica Atenei Parmensis, 2025)
Background: Pulmonary arteriovenous malformations (PAVM) in children is a cardiovascular anomaly characterized by an anatomic communication between the pulmonary artery and pulmonary vein. PAVM is a rare disease, reported more in females. All PAVMs of size at least 3 mm have to be treated to prevent lethal complications such as stroke / brain abscess. Description of procedure: A 3 years old boy weighing 13 kgs experienced easy fatiguability, exertional dyspnea NYHA class II, and delayed milestone. Peripheral oxygen saturation was 72%. Under general anesthesia, a 6French introducer sheath was placed in the right common femoral vein. The right heart was catheterized with a 5F pigtail directed engaged the right pulmonary artery, and pulmonary angiogram showed a connection between pulmonary artery and pulmonary vein. The target vessels for occlusion were the superior (7.6 mm) and inferior (7.7 mm). A 12-10 Konar MFO device was positioned to occlude the connection. Result: Pulmonary angiography showed no residual flow, peripheral oxygen saturation improved significantly to 92% after occlusion. Conclusion: This case demonstrates the feasibility of percutaneous closure of giant PAVM with good result. No mortality or complication were reported up to 4.5 years post procedure.